Visita monitorada à arte possível, uma crítica histórica a partir do acervo do TUCA - Novaes, Luiza Helena (2011)
This paper aims to make a critical historical reading of a selection of artistic performances that took place on the stages of the Teatro da Universidade Católica de São Paulo (TUCA) in different periods. One of the approaches is trying to recover the possible consciousness in the different historical periods as well as in the art made in each of them. We have chosen a somewhat wide time parameter, covering from the 1960s to 2010, mirroring what can be found at the Theater s Archive, which is organized in historical dossiers of the performances held at this university theater of indisputable relevance in São Paulo s history